2018
DOI: 10.1016/j.scitotenv.2018.03.222
|View full text |Cite
|
Sign up to set email alerts
|

Effects of increasing atmospheric CO2 on the marine phytoplankton and bacterial metabolism during a bloom: A coastal mesocosm study

Abstract: Increases of atmospheric CO concentrations due to human activity and associated effects on aquatic ecosystems are recognized as an environmental issue at a global scale. Growing attention is being paid to CO enrichment effects under multiple stresses or fluctuating environmental conditions in order to extrapolate from laboratory-scale experiments to natural systems. We carried out a mesocosm experiment in coastal water with an assemblage of three model phytoplankton species and their associated bacteria under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 80 publications
1
15
0
Order By: Relevance
“…On the other hand, under nutrient replete conditions, growth of diatoms tends to be enhanced (Wu et al, 2014). In coastal eutrophic water, increased partial pressure of CO 2 increased primary production of phytoplankton assemblages dominated by diatoms in a mesocosm study (Huang et al, 2018).…”
Section: Ocean Acidificationmentioning
confidence: 85%
“…On the other hand, under nutrient replete conditions, growth of diatoms tends to be enhanced (Wu et al, 2014). In coastal eutrophic water, increased partial pressure of CO 2 increased primary production of phytoplankton assemblages dominated by diatoms in a mesocosm study (Huang et al, 2018).…”
Section: Ocean Acidificationmentioning
confidence: 85%
“…The planktonic community metabolic rates were estimated from the changes in dissolved oxygen concentrations in the light–dark bottles over a 24‐h incubation period following the procedure of Serret et al (). The dissolved oxygen concentrations were determined by high‐precision Winkler titration (Oudot et al ; Huang et al ) with an automated potentiometric end‐point detection system (Metrohm‐848, Switzerland). For each depth, the water samples were carefully siphoned into 12 calibrated 100 mL borosilicate bottles using silicon tubing, with more than 300 mL overflowing.…”
Section: Methodsmentioning
confidence: 99%
“…Taken together, we inferred that the elevated pCO 2 first delayed growth of DMSP-consuming bacteria; then the delayed DMSP-consuming bacteria postponed the DMSP degradation process, and eventually delayed the DMS concentration in the high pCO 2 treatment. In addition, considering that algae and bacteria in natural seawater were removed through a filtering process before the experiment (Huang et al, 2018), we further concluded that the elevated pCO 2 controlled DMS concentrations mainly by affecting DMSP-consuming bacteria attached to T. weissflogii and P. tricornuntum.…”
Section: Impact Of Elevated Pco 2 On Dms and Dmsp Productionmentioning
confidence: 77%